Computational design of faster rotating second-generation light-driven molecular motors by control of steric effects1. Issue 33 (7th September 2015) - Oruganti, Baswanth; Fang, Changfeng; Durbeej, Bo
<x xml:space="preserve">Abstract</x> By tuning the steric bulkiness of the stereogenic substituent, the rate-determining thermal free-energy barrier of an already MHz-capable rotary molecular motor can be reduced by a further 15–17 kJ mol−1.